2016
DOI: 10.1016/j.envres.2016.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression following cumulative low-level exposure to organophosphate pesticides

Abstract: Previous research suggests that individuals with a prior history of pesticide poisoning are at increased risk of psychiatric disorder (Freire & Koifman, 2013), but findings regarding the impact of cumulative low-level exposure are inconsistent. The aim of the current study was to investigate whether sheep farmers with a history of low-level exposure to organophosphate pesticides (1) report a higher level of psychological distress on subjective symptom questionnaires, compared to unexposed controls (2) also mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 58 publications
4
49
1
8
Order By: Relevance
“…Some studies have identified greater mental health issues and less life satisfaction amongst farmers than non-farmers [13]. The literature suggests that farmers' stress is attributable to pesticide exposure, financial difficulties, climate variability, injuries, regulations, uncertainty about the future, role conflict between work and home roles, and heavy workloads [13][14][15]. Most importantly, mental disorders have been recognised as one of the key risk factors for suicide and suicidal ideation in farmers [13,16].…”
Section: Overall Influences On Farmer Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have identified greater mental health issues and less life satisfaction amongst farmers than non-farmers [13]. The literature suggests that farmers' stress is attributable to pesticide exposure, financial difficulties, climate variability, injuries, regulations, uncertainty about the future, role conflict between work and home roles, and heavy workloads [13][14][15]. Most importantly, mental disorders have been recognised as one of the key risk factors for suicide and suicidal ideation in farmers [13,16].…”
Section: Overall Influences On Farmer Mental Healthmentioning
confidence: 99%
“…One of the most researched aspects of farming and mental health is the link between the use of neurotoxic pesticides and neural systems (not used in certified organic farming) known to cause mental illness and depression [15]. Khan et al [2] found that organic farmers have a significantly lower frequency of neurological symptoms and depression.…”
Section: Potential Influence Of Organic Farming On Mental Healthmentioning
confidence: 99%
“…Adult OP exposure has been associated with adverse neurological outcomes including neuropsychiatric conditions [106], cognitive deficits, and neurodegenerative diseases; for review, see [28,43,107108]. Some studies have failed to detect associations between occupational OP exposure and neurotoxicity, but this could be because the specific type of OP and individual susceptibility/sensitivity factors such as gene polymorphisms are rarely assessed [109].…”
Section: Sex-specific Effects Of Op Exposure In Adulthoodmentioning
confidence: 99%
“…Cognitive and motor difficulties are the most commonly described neurotoxic conditions associated with chronic occupational exposure to OPs (Starks et al 2012;Meyer-Baron et al 2015;Muñoz-Quezada et al 2016a, 2016bCorral et al 2017). Recent studies have also shown OP exposure is related to emotional disturbances (Mackenzie Ross et al 2010;Harrison and Mackenzie Ross 2016), asthma, allergies (Hoppin et al 2009), Parkinson's disease, neuropathy (Povey et al 2014) and cancer (Alavanja and Bonner 2012) and poorer neurodevelopment in children (Bouchard et al 2011;Rauh et al 2012).…”
Section: Introductionmentioning
confidence: 99%